The Tradition of Almsgiving (Infak) from a Sociological Perspective - Cut Luluk Maskuroh (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
This study examined the tradition of infak (almsgiving) from a sociological perspective, analyzing the influence of social norms, cultural values, and social structures that shape its practice within Muslim communities. Infak was understood not only as a religious obligation but also as a social phenomenon that reflected collective moral responsibility, solidarity, and the distribution of welfare in society. Using a qualitative descriptive approach, this study analyzed textual sources, religious teachings, and sociological concepts to understand how the tradition of infak had been formed, maintained, and practiced over time. The findings indicated that social norms rooted in religious teachings strongly encouraged individuals to give infak as a moral duty, creating shared expectations for community members to contribute to social welfare. Cultural values emphasizing compassion, generosity, and mutual assistance further strengthened the continuity of this tradition. The study also revealed that infak played a significant role in reducing social inequality by supporting individuals and groups in vulnerable economic conditions. In addition, infak fostered social cohesion through interactions between donors and recipients, strengthening trust and communal ties. Despite its positive impact, challenges such as limited awareness, inconsistent participation, and economic constraints hindered its optimal implementation. Overall, this study concluded that the tradition of infak was a complex sociological phenomenon that contributed to reinforcing solidarity, justice, and social welfare. Therefore, continuous efforts were needed to promote and institutionalize infak practices to maximize their benefits for society.